Lingkungan Bisnis, Inovasi Produk, Entrepreneurial Secret, Aliansi Stratejik Sebagai Upaya Meningkatkan Keunggulan Kompetitif - Marnoto Marnoto; Sinar Hubtriyan Ade (JURNAL STIE SEMARANG, 2021)
This research aims to analyze the influence of business environment, product innovation and Entrepreneurial Secret to strategic alliance as well Analyzing the influence of the business environment, product innovation, Entrepreneurial Secret and strategic alliances on competitive advantage. This study population is Manager and assistant manager in every area of Bank BCA in Central Java and Yogyakarta period 2020 which amounted to 124 people. The sampling technique in this research uses a sampling census which means the entire population is used as the research sample. This means that the sample used totaled 124 Managers and assistant managers in each area of Bank BCA in Central Java and Yogyakarta. The analytical tool used is Path Analysis. The results of this study indicate that the business environment has a significant effect on strategic alliances. Product innovation has a significant effect on strategic alliances. Entrepreneurial Secret has a significant effect on strategic alliances. The business environment has no effect on competitiveness. Product innovation has no effect on competitiveness. Entrepreneurial Secret has a significant effect on competitiveness. Strategic alliances have a significant effect on competitive advantage.